The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1161/circinterventions.116.004990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Permanent Right Internal Mammary Artery Closure on Coronary Collateral Function and Myocardial Ischemia

Abstract: Background—The objective of this study is to test the effect of permanent right internal mammary artery device closure on coronary collateral function and myocardial ischemia.Methods and Results—This was a prospective, open-label clinical trial in 50 patients with coronary artery disease. The primary study end point was coronary collateral flow index as obtained during a 1-minute proximal right coronary artery (RCA) and left coronary artery balloon occlusion at baseline before and at follow-up examination 6 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Recently investigated have been the function of mammary‐to‐coronary artery anastomoses and their effects on myocardial ischemia in humans by occluding the IMAs with an angioplasty balloon. In the presence versus absence of IMA occlusion, the collateral flow index was significantly higher, intracoronary ECG ST elevation significantly less, and angina diminished while occluding the right IMA for 3 weeks even improved fractional flow reserve . Hence, these studies have confirmed the theory that a functional ischemia‐reducing extracardiac coronary artery supply exists via naturally‐occurring IMA anastomoses.…”
Section: Commentsupporting
confidence: 57%
“…Recently investigated have been the function of mammary‐to‐coronary artery anastomoses and their effects on myocardial ischemia in humans by occluding the IMAs with an angioplasty balloon. In the presence versus absence of IMA occlusion, the collateral flow index was significantly higher, intracoronary ECG ST elevation significantly less, and angina diminished while occluding the right IMA for 3 weeks even improved fractional flow reserve . Hence, these studies have confirmed the theory that a functional ischemia‐reducing extracardiac coronary artery supply exists via naturally‐occurring IMA anastomoses.…”
Section: Commentsupporting
confidence: 57%
“…[ 5 ] The collateral flow index, fractional flow reserve, intracoronary ECG, and anginal symptoms have all been recently demonstrated to improve when the ipsilateral IMA is occluded. [ 6 ] These recent findings confirm that the old principle of IMA occlusion had a strong rationale, and suggest that it would be worthwhile further studying its effects in RA.…”
mentioning
confidence: 59%
“…In comparison, the absolute change in CFI during short‐term treatment with G‐CSF was +0.049 ± 0.062 (−0.010 ± 0.060 in the placebo group), whereby the CFI responses during follow‐up were more consistent, and thus, statistically more relevant in the previous than the actual study. The average CFI response to other forms of coronary arteriogenesis, such as heart rate reduction by ivabradine, physical exercise, external counterpulsation, or extracardiac coronary collateral supply augmentation via the native internal mammary artery compares as follows: +0.059 ± 0.050, +0.069 ± 0.050, and +0.067 ± 0.064, respectively. Thus, the effects appear more sizeable and less variable than the response induced by pegfilgrastim, both of which may be related to a possible fading effect of the pro‐arteriogenic action of pegfilgrastim linked to a longer period of administration over 6 months vs only 6 weeks to 3 months.…”
Section: Discussionmentioning
confidence: 99%